Lack of long‐term add‐on effect by montelukast in postoperative chronic rhinosinusitis patients with nasal polyps. (8th November 2017) - Van Gerven, Laura; Langdon, Cristobal; Cordero, Arturo; Cardelús, Sara; Mullol, Joaquim; Alobid, Isam
Abstract : Objectives/Hypothesis: Eosinophils and mast cells are among the key cells in inflammatory diseases like chronic rhinosinusitis (CRS) and asthma. Leukotriene antagonists have proven to be effective in the treatment of asthma, but data about their efficacy in CRS are scarce, whereas data on montelukast as an add‐on treatment to intranasal corticosteroids (INCS) in a postoperative setting are completely lacking. Study Design: Prospective, randomized, open‐label trial. Methods: In this trial with long‐term follow‐up, we evaluated the efficacy of montelukast as an add‐on treatment to INCS in postoperative CRS with nasal polyp (CRSwNP) patients. CRSwNP patients (N = 72) undergoing endoscopic sinus surgery were randomized in two arms for the postoperative treatment. One group (N = 36) received INCS in monotherapy, whereas the other group (N = 36) received INCS in association with montelukast for 1 year. The efficacy of montelukast with INCS was evaluated by assessing both subjective (total five‐symptom score [T5SS]) and objective (nasal polyp score [NPS], Lund‐Mackay [LMK] score, and subjective olfactometry [Barcelona Smell Test 24]) outcome parameters and compared with the gold standard of INCS in monotherapy. Results: After 1 year of surgery, T5SS, NPS, and LMK score were significantly reduced in patients treated with either INCS or INCS plus montelukast, without significant differences between the two treatment arms. Improvement of smell loss by olfactometry was also observed with no differences between arms. Similar findings were observed at 3 and 6 months. Conclusions: These results suggest that the addition of montelukast to INCS should not be recommended in the treatment of postoperative CRSwNP patients. Level of Evidence: 1b Laryngoscope, 1743–1751, 2018